Azidoborolate anions and azidoborole adducts: isolable forms of an unstable borole azide. Issue 30 (24th March 2022) - Lindl, Felix; Fantuzzi, Felipe; Mailänder, Lisa; Hörl, Christian; Bélanger-Chabot, Guillaume; Braunschweig, Holger
Abstract : An unstable azidoborole derivative was prepared and indirectly identified through trapping in the form of neutral Lewis adducts and, quite surprisingly, in the form of the diazidoborolate complex anion. Abstract : Boroles are well known to undergo ring expansion reactions with organic azides to yield 1, 2-azaborinines. A synthon featuring both azide and borole moieties within the same molecule, 1-azido-2, 3, 4, 5-tetraphenylborole, was found to be much less stable than the related, previously-reported azidoborafluorene and decomposed to intractable mixtures well below room temperature. It could, however, be trapped at −75 °C through the formation of Lewis base adducts, even in the form of the "azide-stabilized azidoborole" complex anion diazidoborolate. DFT calculations provide a rationale for the low stability of the azidoborole under study.